A Multicenter Real-World Study Evaluating the Hepatoprotective Effect of Polyene Phosphatidylcholine Against Chronic Hepatitis B - Xu, Jinghang; Fan, Yanan; Yu, Yanyan; Han, Yifan; Kang, Qian; Tan, Ning; Yang, Yuqing; Chen, Hongyu; Pan, Jiali; Xu, Xiaoyuan (Frontiers in Medicine, 2022)
Background:Polyene phosphatidylcholine(PPC) has been widely used to treat liver diseases in China.However,there is a lack of post-marketing evidence demonstrating its liver-protective efficiency among patients infected with hepatitis B virus(HBV). This study analyzed the multicenter real-world data to compare the effectiveness of PPC with those of magnesium isoglycyrrhizinate(IsoMag) and glutathione(GSH) in patients with liver injury. Methods:This study comprised the real-world data analysis of a multicenter, retrospective observational cohort. The data were retrieved from the Cooperative Registry of the Hospital Prescription in China between October1,2018, and September 30, 2019.A growth curve analysis was performed to compare the effects of different treatments on liver function longitudinally for up to 30 days after treatment commencement. In addition, the dose-effect of the PPC treatment was investigated. Results:The final cohort included 6,052 patients with approximately 8% infected with HBV(N=471).There were 1,649, 1,750,and2,653 patients in the PPC,GSH,and IsoMag groups, respectively, with an average age of 53.9years.In patients withHBV infection,the PPC treatment was associated with a significant decline in alanine aminotransferase(ALT) and aspartate aminotransferase(AST)levels(slopes:−3.7, 95%Cl−6.0to−1.5U/L/day;−2.4, 95%Cl−4.5to−0.3 U/L/day,respectively). However, there were no significant differences in the effects among the three groups. In patients without HBV infection, the PPC treatment decreased ALT, AST, γ-glutamyl transferase(GGT)and albumin level(−5.2,95%CI−5.8to−4.5U/L/day;−3.5,95% CI−4.2to−2.7U/L/day; −4.9, 95%CI−6.2to−3.7U/L/day,-0.07,95%CI-0.09to-0.04 g/L/day, respectively) and showed a stronger effect on lowering ALT levels than GSH (−2.6,95%CI−3.3to−1.8U/L/day,P<0.05) as well as a stronger effect on lowering GGT levels than IsoMag(−1.4,95%CI−2.4to−0.4U/L/day,P<0.05). PPC had no impact on prothrombin activity levels in patients with or without HBV infection. High-dose PPC exhibited a stronger effect on lowering ALT and AST levels than low-dose PPC. Conclusion:This was the first real-world multicenter study to demonstrate that PPC efficiently lowers ALT and AST levels in patients with liver diseases regardless of the status of HBV infection. PPC treatment showed a comparable or better effect compared with GSH and IsoMag treatments. High-dose PPC resulted in a stronger effect than low-dose PPC.